Healthcare Resource Utilization and Costs Associated with Autosomal Dominant Polycystic Kidney Disease - Christopher M. Blanchette; Şerban R. Iorga; Aylin Altan; Jerry G. Seare; Ying Fan; Sandro Rossetti; Benjamin Gutierrez (Journal of Health Economics and Outcomes Research)
**Background:** Autosomal dominant polycystic kidney disease (ADPKD), a hereditary nephropathy, eventually leads to end-stage renal disease (ESRD), typically by mid-life.